Efeitos da exposição a mudanças nas contingências sobre o seguir regras - ALBUQUERQUE, Luiz Carlos de (2016)
By investigating the effects of experimental histories on discrepant rule following contingencies, nine university students were exposed to a matching-to-sample procedure; the task was to point out, in a set order, it one of three comparison stimuli. Each condition comprised four sessions. The contingencies in Session 1 were altered in Session 2, reestablished in Session 3 and remained unchanged in Session 4, which began with the discrepant rule. The three conditions differed as to the form of establishment of the alternative behavior to that specified by the discrepant rule. Independent of how the behavior was established in Session 1, whether by contingencies (Condition 1) or by rules (Conditions 2 and 3), only those participants who responded correctly in Sessions 2 and 3 (n = 7) did not follow the discrepant rule in Session 4. It is also discussed some of the characteristics that an experimental history should have to interfere with discrepant rule following.